1998
DOI: 10.1177/030006059802600203
|View full text |Cite
|
Sign up to set email alerts
|

Adequate Relief as an Endpoint in Clinical Trials in Irritable Bowel Syndrome

Abstract: Irritable bowel syndrome is characterized by recurrent abdominal pain and altered bowel function. In designing studies to evaluate new treatments for this disease, however, it is difficult to select appropriate endpoints to reflect improvement in the range of symptoms of the syndrome. In the present study we evaluated the parameter of adequate relief of abdominal pain and discomfort, as perceived by the patients, as a key endpoint for efficacy in the treatment of patients with irritable bowel syndrome. Abdomin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
87
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(87 citation statements)
references
References 7 publications
0
87
0
Order By: Relevance
“…This study utilized “adequate relief” as its primary outcome, which has been used and accepted in other functional GI trials such as IBS. 23, 40 Although Rome III criteria were not applied because the study began prior to their publication, the present data suggest epigastric pain syndrome and ulcer-like dyspepsia cover similar domains. This study’s execution and interpretation of results were regularly overseen by the National Institutes of Health and the Data and Safety Monitoring Board.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…This study utilized “adequate relief” as its primary outcome, which has been used and accepted in other functional GI trials such as IBS. 23, 40 Although Rome III criteria were not applied because the study began prior to their publication, the present data suggest epigastric pain syndrome and ulcer-like dyspepsia cover similar domains. This study’s execution and interpretation of results were regularly overseen by the National Institutes of Health and the Data and Safety Monitoring Board.…”
Section: Discussionmentioning
confidence: 67%
“…22, 23 This self-report measure is considered clinically relevant and has been tested for responsiveness in FD. 24, 25 The disease-specific validated Nepean Dyspepsia Index (NDI) was used to assess FD quality-of-life 26 at baseline and post-treatment.…”
Section: Methodsmentioning
confidence: 99%
“…Mangel et al [22] found that adequate relief of abdominal pain is significantly correlated with changes in the multiple parameters associated with IBS (such as changes in bowel habit, incomplete emptying and bloating) and can be used as an endpoint for assessing response to therapy. In our series 70% claimed the abdominal pains were less frequent, and 69% gave high scores for the overall improvement in their IBS symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Global Improvement will be assessed with the Global Improvement Scale ( GIS ) . This scale asks participants "Compared to the way you felt before you entered the study, have your IBS symptoms over the past 7 days been from (1) = substantially worse, to (7) = substantially improved [95]". Global improvement is noted for patients endorsing moderately or substantially improved status.…”
Section: Primary Outcomesmentioning
confidence: 99%
“…Global improvement is noted for patients endorsing moderately or substantially improved status. The scale shows adequate reliability and validity [95]. Global improvement, in addition to symptom severity, is recommended as a primary endpoint in IBS therapy trials [96].…”
Section: Primary Outcomesmentioning
confidence: 99%